Mupirocin-Resistant Staphylococcus aureus in Iran: A Biofilm Production and Genetic Characteristics. (15th January 2022) - Zamani, Samira; Mohammadi, Anis; Hajikhani, Bahareh; Abiri, Parnaz; Fazeli, Maryam; Nasiri, Mohammad Javad; Dadashi, Masoud; Goudarzi, Mehdi; Haghighi, Mehrdad
Abstract : The spread of mupirocin-resistant Staphylococcus aureus strains in hospitals and communities is a universal challenge. Limited data is available on the genetic features of high-level mupirocin resistant- (HLMUPR-) S. aureus isolates in Tehran. In the present research, we investigated 48 high-level mupirocin resistance S. aureus by antimicrobial activity, virulence analysis, biofilm formation, multilocus sequence typing (MLST), and staphylocoagulase (SC) typing. All the HLMUPR strains were positive for mupA gene. The frequency of multidrug resistance was 97.9%. Twenty-one (43.8%) were toxinogenic with 14 producing pvl (29.2%), 5 tst (10.4%), and two eta (4.2%). Among the HLMUPR isolates, biofilm production was detected in 45 (89.6%) isolates with complete dominance clfB, clfA genes, and a noticeably high frequency fnbA (95.8%), followed by fnbB (93.8%), eno and icaD (each 83.3%), sdrC (81.3%), ebps (79.2%), icaA (75%), sdrD (66.7%), fib (60.4%), sdrE (50%), cna (41.7%), and bap (4.2%). Coagulase typing distinguished isolates into four genotypic patterns including III (50%), II (27.1%), and type IVa (22.9%). A total of three clonal complexes (CCs) and 4 sequence types (STs) including CC/ST22 as the most prevalent (52.1%), CC8/ST239 (20.8%), CC/ST8 (16.7%), and CC/ST5 (10.4%) were identified in current work. According to our analysis, nonbiofilm producer isolates belonged to CC8/ST239 (6.3%) and CC/ST8 (4.2%). Fusidic acid-resistant isolates belonged to CC/ST45 (n = 3 ) and CC8/ST239 (n = 1 ). Observations highlighted the circulation of the CC/ST22 HLMUPR S. aureus strains with strong biofilm-production ability in our hospitals, indicating the possibility of transmission of this type between community and hospital.